Traditional Chinese medicine polysaccharide dressing for diabetic wound healing and preparation method
By combining pectin polysaccharide nanofibers with a composite gel matrix, and employing a Mg-Zn composite nanosystem and dual cross-linking technology, the stability and biocompatibility issues of diabetic wound dressings were resolved, achieving uniform encapsulation and controlled release of drugs, and promoting rapid healing of diabetic wounds.
Patent Information
- Application Number
- CN202511886395.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-02-06
AI Technical Summary
Existing diabetic wound dressings suffer from unstable drug embedding, weak bonding between the gel matrix and nanofiber layer, simple cross-linking structure, and biocompatibility risks. Furthermore, they lack mechanical strength in hypertonic environments, affecting efficacy and safety.
By using pectin polysaccharide nanofibers and a composite gel matrix, a porous network structure is formed through electrospinning. Combined with a Mg-Zn composite nanosystem, Ca²⁺ ions and glutaraldehyde are used for double cross-linking. In addition, surface modifiers and humectants are added to form a stable polysaccharide dressing, which achieves uniform encapsulation and controlled release of drugs.
It achieves stable encapsulation and controlled release of drugs, enhances the mechanical strength and biocompatibility of dressings, significantly promotes the healing of diabetic wounds, reduces oxidative stress and inflammation, and improves wound healing efficiency.
Smart Images

Figure CN121466348A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of medical dressings, and relates to a traditional Chinese medicine polysaccharide dressing for diabetic wound healing and a preparation method. BACKGROUND
[0002] Diabetic wounds exhibit characteristics such as delayed healing, susceptibility to infection, and prolonged inflammation due to long-term high-sugar environment, vascular lesions, and low immune function. To improve the healing environment, existing technologies often use drug-containing gels, nanofiber membranes and other local drug delivery carriers for drug delivery and wound protection. However, existing polysaccharide-based nanofiber and gel dressings have various shortcomings, such as unstable embedding of effective substances. Because the existing gel system is mostly a single polymer network structure, the effective components of traditional Chinese medicine are easily affected by changes in external humidity, temperature and pH during storage or use, leading to drug leakage or degradation. Drug-containing nanofiber structures are easily collapsed in a swelling or wet environment, resulting in uncontrollable drug release curves and affecting the sustained efficacy. For example, the gel matrix is not firmly combined with the nanofiber: in existing processes, most adopt the simple means of coating drug-containing gel on the surface of the fiber membrane, lacking interface chemical bond connection, which leads to easy peeling and cracking of the gel layer during use, reducing the overall stability of the dressing and drug utilization rate. As an improvement, some nanofibers are modified on the surface, and the common method is crosslinking. However, single ion or chemical crosslinking leads to insufficient stability of the fiber network or excessive brittleness, and there is also a risk that improper selection and solvent cutoff of the crosslinking agent will not be completely removed after crosslinking, posing potential cytotoxicity and biological safety hazards. Even some wound dressings claim to solve some of the above problems, but diabetic wounds are special, with high seepage, obvious pain and local high fever. To address the above issues, existing technologies increase the proportion of hydrogel or add some moisturizing components, but using high levels of moisturizers leads to a decrease in the mechanical strength of the fiber membrane, making it prone to rupture. More importantly, uneven mixing of moisturizers and gel matrix can also affect drug loading and release performance.
[0003] Therefore, there is an urgent need in the art for a new traditional Chinese medicine polysaccharide dressing that can stably embed active ingredients in its structure, enhance the bonding force of the gel matrix and the nanofiber layer, and have controllable crosslinking and safety protection. SUMMARY
[0004] The application provides a traditional Chinese medicine polysaccharide dressing for diabetic wound healing and a preparation method, which can solve the problems of poor embedding stability, poor bonding of the gel matrix and the nanofiber layer, single crosslinking structure and biological compatibility risk in the prior art.
[0005] To achieve the above-mentioned purpose, the application adopts the following technical solutions:
[0006] A traditional Chinese medicine polysaccharide dressing for diabetic wound healing, the dressing is composed of pectin polysaccharide nanofiber, composite gel matrix, and auxiliary agent;
[0007] The composite gel matrix is a porous network gel structure embedding traditional Chinese medicine extract, and the pectin polysaccharide nanofiber is formed by electrospinning of pectin polysaccharide and polymer under the action of crosslinking agent and surfactant.
[0008] The pectin polysaccharide is selected from pitaya peel pectin, orange peel pectin, and apple peel pectin.
[0009] The auxiliary agent is one of adhesive, humectant, compatibilizer, or surface modifier.
[0010] The traditional Chinese medicine extract includes one or more of Huangbai extract, Zhizi extract, and Naringin extract.
[0011] The traditional Chinese medicine polysaccharide dressing is in the form of film or patch, and the thickness is 0.3-1.2 mm.
[0012] The pitaya peel pectin polysaccharide contains not only abundant pectin but also about 34.35% of cellulose, has complex molecular structure, and has high molecular chain rigidity and space skeleton stability due to the diversity of glycosidic bond connection. The medium esterification degree keeps the balance between intermolecular electrostatic repulsion and hydrophobic interaction, and the formed entangled network is more stable, which is conducive to the formation of uniform and excellent mechanical property nanofiber in the electrospinning process and the stable support in the subsequent grafting and embedding of Mg-Zn composite nanosystem.
[0013] Preferably, the polymer is one of polyvinyl alcohol (PVA), polyethylene oxide (PEO), chitosan, chitin, or gelatin.
[0014] Preferably, the crosslinking agent includes one of calcium ion, glutaraldehyde, or adipic acid dihydrazide; and the surfactant is Triton X-100.
[0015] Preferably, the adhesive is low molecular weight polyvinyl alcohol or hydroxypropyl methyl cellulose; and the humectant is glycerol or sodium hyaluronate.
[0016] The above technical solution enhances the adhesion of the dressing to the wound surface, seals the wound microenvironment, and is conducive to maintaining local hypoxia / hydration to promote HIF-1 related angiogenesis. HIF-1 is a key factor in wound angiogenesis, and the dressing maintains appropriate oxygen tension and moisture, which helps its local activity. The moist environment is conducive to cell migration / re-epithelialization and reduces necrosis, and moisture can reduce oxidative stress load, thereby indirectly maintaining Nrf2 function and inhibiting ROS.
[0017] Preferably, the compatibilizer is polyethylene oxide or polyethylene glycol.
[0018] Preferably, the surface modifier includes one or more of low temperature plasma, acrylic acid, glycidyl acrylate to introduce carboxyl, hydroxyl or epoxy functional groups.
[0019] The above technical solution can realize the directional release or fixed embedding of the effective substance through grafting, directly acts on the upstream mechanism, promotes angiogenesis and reduces oxidative stress.
[0020] The application also provides a method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing, comprising the following steps:
[0021] S1: extracting pitaya pectin polysaccharide, concentrating, alcohol precipitating, drying and crushing the pectin solution into pectin polysaccharide dry powder for standby;
[0022] S2: adding the pectin polysaccharide dry powder, at least one polymer and at least one crosslinking agent to a solvent, the solvent being water or a water / alcohol mixed solvent, and adding a cosolvent DMSO, stirring and heating to uniform dissolution or dispersion to prepare a solution;
[0023] S3: electrospinning the solution to obtain polysaccharide nanofibers;
[0024] S4: performing surface modification treatment on the polysaccharide nanofibers to introduce active functional groups;
[0025] S5: performing chemical grafting treatment on the modified polysaccharide nanofibers, and embedding an Mg-Zn composite nanosystem in the grafting process to make it uniformly distributed in the nanofiber layer;
[0026] S6: embedding traditional Chinese medicine extract in a gel matrix by an ultrasonic-assisted swelling method or a freeze-drying method to prepare a composite gel matrix, adding an adhesive, a humectant and a compatible agent to the composite gel matrix in turn, stirring uniformly, and then compounding the nanofiber layer obtained in step S5 by a coating, dipping or laminating method, and forming a dressing by freeze-drying or mild drying.
[0027] Preferably, the nanofiber surface is chemically grafted with acrylic acid or glycidyl acrylate in S5, and the grafting monomer accounts for 1-10 mol% of the surface available functional groups.
[0028] Preferably, in step S2, the concentration of the pectin solution is 6-10 wt%; 6 wt%, 8 wt% and 10 wt% pectin solutions are prepared respectively, and 1M NaOH is added to adjust the pH to neutral.
[0029] In the above technical solution, calcium ions are mainly crosslinked with carboxyl groups, and the pectin contains a large number of ester groups; the pH is adjusted to neutral to promote the hydrolysis of the ester groups to form carboxyl groups for calcium ion crosslinking.
[0030] Further, the cross-linking agent is preferably double cross-linked by Ca²⁺ and glutaraldehyde. When ionically cross-linked, Ca²⁺ accounts for 0.5-2.0 wt% of the solid content of the solution; when chemically cross-linked, glutaraldehyde is vapor-phase cross-linked at room temperature for 12-24 h, with a glutaraldehyde solution concentration of 25-50%, placed at the bottom of the container; when the glutaraldehyde solution is cross-linked, the polysaccharide nanofiber is immersed in the glutaraldehyde solution for reaction, accounting for 0.1-1.0 wt% of the solid content of the solution, at 25-37℃ for 2-6 h.
[0031] By adopting the above technical solution, the gas phase method is suitable for maintaining the fiber morphology, and the solution method is suitable for surface modification and functionalization steps.
[0032] Further, the gas-phase cross-linking and solution cross-linking are graded, wherein the polysaccharide nanofiber is washed with 0.1M ethanolamine or repeated PBS after glutaraldehyde cross-linking and then vacuum dried until the residual amount is less than 0.05 wt% to ensure biocompatibility.
[0033] Preferably, the amount of the compatibilizer added in step S6 is 1-10 wt% of the total mass of the dressing; the amount of the humectant added is 0.1-15 wt% of the total mass of the dressing; and the amount of the adhesive added is 2-8 wt% of the total mass of the dressing.
[0034] Further, when the humectant is glycerol, the mass accounts for 5-15 wt% of the gel matrix; or when the humectant is sodium hyaluronate, the amount accounts for 0.1-1.0 wt% of the gel matrix.
[0035] Preferably, in step S3, the electrospinning voltage is 15-25 kV, the collection distance is 10-20 cm, the solution flow rate is 0.2-1.0 mL / h, the spinning time is 1-3 h per layer; the cross-linking temperature is 25-50℃, and the cross-linking time is 10 min-24 h.
[0036] The receiving speed is 80-120 r / min, preferably 100 r / min;
[0037] The translation speed is 280-320 mm / min, preferably 300 mm / min;
[0038] The ambient temperature is 20-40℃, preferably 25-35℃;
[0039] The relative humidity is 30-70%, preferably 35-50%, to ensure the stability of the fiber morphology and porosity;
[0040] The cross-linking temperature is 25-50℃, and the cross-linking time is 10 min-24 h, wherein the ionically cross-linked time is 10-60 min, and the chemically cross-linked time is 2-24 h, and the cross-linking agent is washed during post-processing.
[0041] Preferably, in step S2, the mass ratio of polysaccharide to polymer is 1:(1-4), and the average diameter of the obtained nanofiber is 100-500 nm; the concentration of the traditional Chinese medicine extract is 1-5 wt% of the dry weight of the gel matrix.
[0042] Preferably, the Mg-Zn composite nano system is a composite of magnesium-based metal organic framework (Mg-MOF) and zinc oxide nanoparticles, and the embedding amount is 0.1-5 wt% of the mass of the polysaccharide nanofiber.
[0043] Advantages of the present application:
[0044] 1) The hylocereus pectin polysaccharide has a complex molecular structure, high chain rigidity, moderate esterification degree, and balanced intermolecular electrostatic and hydrophobic interactions, and can form a uniform and stable entangled network structure in the electrospinning process, thereby endowing the nanofiber with excellent mechanical properties and morphology retention, and the polysaccharide nanofiber has high structural stability and high biocompatibility;
[0045] 2) The pectin polysaccharide nanofiber, the traditional Chinese medicine extract and the Mg-Zn composite nano system have a significant synergistic effect, the pectin polysaccharide nanofiber provides a structural support and a slow-release platform, the traditional Chinese medicine extract provides anti-inflammatory, antibacterial and antioxidant effects, and the Mg-Zn composite nano system promotes collagen deposition, inhibits excessive inflammation and active oxygen (ROS) accumulation. It is found through comparison that the ternary system is significantly better than the single component and the binary combination in many indicators, and is higher than the Bliss additive expectation value, proving that the three have a synergistic effect at the molecular and tissue repair level, and can realize multi-pathway intervention of the oxidative stress, inflammation and matrix degradation of the diabetic wound;
[0046] 3) The Mg-Zn composite nano system composed of Mg-MOF and ZnO nanoparticles is embedded in the grafting process, and realizes double slow release by combining with the porous gel matrix, thereby achieving the multiple therapeutic effects of antibiosis, pro-angiogenesis and anti-inflammation;
[0047] 4) The Ca²⁺ ion crosslinking and glutaraldehyde chemical crosslinking double methods are adopted, the Ca²⁺ quickly forms a primary network structure, and the glutaraldehyde further enhances the chemical stability; the chemical crosslinking can be a gas phase method and a solution method, the gas phase method maintains the fiber morphology, and the solution method is suitable for surface modification and functionalization;
[0048] 5) The electrospinning flow rate, temperature and humidity are controlled in grades, different diameters (100-500 nm) of fibers can be prepared, and different release and mechanical requirements can be met; the proportions of the humectant (glycerol or sodium hyaluronate), the adhesive and the compatible agent are optimized, and the moisture retention and mechanical properties are balanced. BRIEF DESCRIPTION OF DRAWINGS
[0049] Figure 1 Healing diagram for animal models;
[0050] Figure 2 Cell compatibility (MTT and Live / Dead) atlas group drawing;
[0051] Figure 3 Single-component system and ternary composite system comparison group drawing in terms of ROS scavenging, MMP-9 down-regulation, and wound closure rate;
[0052] Figure 4 Spinning fiber electron microscope drawing. DETAILED DESCRIPTION
[0053] The present application will be further described below through specific examples. In order to make the inventive purpose, technical scheme and beneficial technical effects of the present application clearer, the present application will be further described in detail below in combination with examples. It should be understood that the examples described in the present specification are only for the purpose of explaining the present application, and are not intended to limit the present application.
[0054] Unless otherwise stated, all adhesive films and reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0055] Example 1:
[0056] 1) Raw material preparation
[0057] The pitaya peel was washed, cut and shredded, and pectin was extracted in a water bath at 80°C. The pectin polysaccharide dry powder was obtained by concentration, alcohol precipitation (95% ethanol), drying and pulverization, with an esterification degree of 53.2% and a cellulose content of 34.35%;
[0058] Polymer: PVA, molecular weight 85,000-124,000, alcoholysis degree 98%;
[0059] Crosslinking agent: CaCl2, 0.5wt%, relative solution solid content; and glutaraldehyde, 0.1wt%, relative solution solid content;
[0060] Humectant: glycerol 5wt%;
[0061] The traditional Chinese medicine extract was a cortex phellodendri extract, which was extracted with ethanol as the solvent, and the total flavonoid content was about 40%;
[0062] Mg-Zn composite nano system: Mg-MOF (150nm) and ZnO (50nm) mass ratio 1:1.
[0063] 2) Preparation of electrospinning solution
[0064] Pectin polysaccharide and PVA were mixed in a mass ratio of 1:1, water was added, stirred and heated to 80°C for dissolution;
[0065] CaCl2 solution (0.5wt%) was added and reacted at room temperature for 30 min;
[0066] Cooling to 25℃, glutaraldehyde solution (0.1wt%) was added and stirred for 10 min.
[0067] 3) Electrospinning
[0068] Voltage 15kV, collection distance 10cm, flow rate 0.2mL / h;
[0069] Ambient temperature 20℃, humidity 30%; spinning for 1h to obtain nanofiber membrane with diameter of about 100nm.
[0070] 4) Surface modification and grafting
[0071] Low temperature plasma treatment for 30s to introduce carboxyl / hydroxyl groups;
[0072] Grafting with glycidyl acrylate, monomer accounting for 1mol% of available functional groups, and embedding Mg-Zn composite system accounting for 0.1wt% of nanofiber mass;
[0073] 5) Composite gel preparation and compounding
[0074] Gelatin-sodium hyaluronate (4:1) as matrix, ultrasonic embedding of Cortex Phellodendri extract 3wt%, accounting for dry gel weight;
[0075] Add glycerol 5wt%, PEG (1wt%), low molecular weight PVA (2wt%) and stir evenly;
[0076] Laminated compounding, freeze-dried into dressing, thickness 0.3mm.
[0077] Example 2: The same as the steps in Example 1, the difference is:
[0078] Crosslinking agent: CaCl2 (1.0wt%), glutaraldehyde (gas phase method, 25% solution placed at the bottom of a sealed container, reacted at room temperature for 12h);
[0079] After crosslinking, neutralize with 0.1M ethanolamine for 1h, then wash with PBS for 3 times and vacuum dried;
[0080] Electrospinning: voltage 20kV, collection distance 15cm, flow rate 0.5mL / h; temperature 30℃, humidity 45%; fiber diameter about 300nm;
[0081] Moisturizer: glycerol, 10wt%; product thickness 0.8mm.
[0082] Example 3: The same as the steps in Example 1, the difference is:
[0083] Crosslinker: CaCl2(2.0 wt%), glutaraldehyde, 1.0 wt%, solution method, 37 °C, 6 h;
[0084] Electrospinning: voltage 25 kV, collection distance 20 cm, flow rate 1.0 mL / h; temperature 35 °C, humidity 60%; fiber diameter about 500 nm;
[0085] Moisturizer: sodium hyaluronate, 1.0 wt% in gel matrix; product thickness 1.2 mm.
[0086] Example 4: same as Example 1 step, except that:
[0087] Crosslinker: CaCl2(0.5 wt%), glutaraldehyde, vapor method, 25% solution, room temperature 24 h;
[0088] Electrospinning: voltage 15 kV, collection distance 10 cm, flow rate 0.2 mL / h; temperature 25 °C, humidity 35%; fiber diameter about 120 nm;
[0089] Moisturizer: sodium hyaluronate (0.1 wt%); product thickness 0.4 mm.
[0090] Example 5: same as Example 1 step, except that:
[0091] Crosslinker: CaCl2(1.5 wt%), glutaraldehyde, 0.5 wt%, solution method, 30 °C, 4 h;
[0092] Electrospinning: voltage 20 kV, collection distance 15 cm, flow rate 0.5 mL / h; temperature 28 °C, humidity 40%; fiber diameter about 250 nm;
[0093] Moisturizer: glycerol (8 wt%) + sodium hyaluronate (0.5 wt%);
[0094] Product thickness 0.9 mm.
[0095] Example 6: same as Example 1, but spinning flow rate changed to 1.0 mL / h, fiber diameter about 500 nm.
[0096] Example 7: same as Example 3, but relative humidity changed to 35%, fiber surface smooth without adhesion.
[0097] Example 8: same as Example 2, but crosslinking time extended to 24 h, vapor method, fiber crosslinking density increased, swelling rate decreased by 15%.
[0098] Example 9: same as Example 4, but CaCl2 content changed to 2.0 wt%, initial ionic crosslinking strength increased.
[0099] Example 10: Same as example 5, but the moisturizer is only glycerin, 15 wt%, the dressing moisture retention is increased by 10%.
[0100] Example 11, same as example 1 step, the difference is:
[0101] 1) Raw material preparation
[0102] Orange peel is washed and shredded, and pectin is extracted in a water bath at 80°C. After concentration, alcohol precipitation (95% ethanol), drying and grinding, the dry powder of pectin polysaccharide is obtained;
[0103] 2) Preparation of 6 wt% pectin solution
[0104] 1.14 g of pectin is dissolved in 17.86 ml of water. After complete dissolution, 1M NaOH is added to adjust the pH to neutral,
[0105] 0.05 g of PEO is dissolved in 0.95 ml of water, and 5 wt% PEO solution (5000 KDa) is mixed uniformly according to the ratio of pectin to PEO of 95:5. After uniform mixing, 0.2 ml of Triton X-100 and 1 ml of DMSO are added and stirred overnight;
[0106] 3) Preparation of spinning, the spinning parameters are as follows
[0107] Needle: 19 gauge stainless steel needle;
[0108] Translation distance: 30 mm;
[0109] Receiving distance: 18 cm;
[0110] Temperature: 32°C;
[0111] Humidity: 55%;
[0112] Receiving speed: 100 r / min;
[0113] Translation speed: 300 mm / min;
[0114] Single crosslinking, calcium chloride crosslinking: dry the fiber in anhydrous ethanol for 5 min at room temperature; after taking out, soak in a mixed solution of 40 wt% calcium chloride aqueous solution and anhydrous ethanol (volume ratio of 5:95) for 20 min; then, soak the fiber in 40 wt% calcium chloride aqueous solution for 2 h; finally, wash with pure water for more than 5 times to remove residual calcium chloride.
[0115] Example 12, same as example 1 step, the difference is:
[0116] 1) Raw material preparation
[0117] Orange peel was washed and cut into pieces, and pectin polysaccharide dry powder was obtained by extracting pectin in a water bath at 80°C, concentrating, alcohol precipitation (95% ethanol), drying and crushing.
[0118] 2) 8 wt% pectin + 5 wt% PEO (95:5) was configured
[0119] 1.52 g of pectin was dissolved in 17.48 ml of water, and after complete dissolution, the PH was adjusted to neutral, 0.05 g of PEO was dissolved in 0.95 ml of water
[0120] Single crosslinking, adipic acid dihydrazide crosslinking: 5mM hydroxybenzotriazole (HOBt) was added to 0.1 M MES buffer (PH=6.5), and after it was dissolved, the fiber was soaked for 2h, then 5mM EDC was added to the reaction solution, and soaked for 1h; 10 mM adipic acid dihydrazide (ADH) was added and soaked for 24h; finally, it was washed with clean water.
[0121] Example 13, the same as step of example 1, the difference is:
[0122] 1) Raw material preparation
[0123] Apple peel was washed and cut into pieces, and pectin polysaccharide dry powder was obtained by extracting pectin in a water bath at 80°C, concentrating, alcohol precipitation (95% ethanol), drying and crushing.
[0124] 2) 10 wt% pectin + 5 wt% PEO (95:5) was configured
[0125] 1.9 g of pectin was dissolved in 17.1 ml of water, and after complete dissolution, the PH was adjusted to neutral, 0.05 g of PEO was dissolved in 0.95 ml of water
[0126] Single crosslinking, adipic acid dihydrazide crosslinking: 5mM hydroxybenzotriazole (HOBt) was added to 0.1 M MES buffer (PH=6.5), and after it was dissolved, the fiber was soaked for 2h, then 5mM EDC was added to the reaction solution, and soaked for 1h; 10 mM adipic acid dihydrazide (ADH) was added and soaked for 24h; finally, it was washed with clean water.
[0127] Comparative example 1: the steps, component parameters are consistent with example 1, but there is no Mg-Zn composite nano system.
[0128] Comparative example 2: the steps are consistent with example 1, and the crosslinking agent is replaced by a single low-toxicity crosslinking agent EDC.
[0129] Comparative example 3: remove only pectin polysaccharide nanofiber (single fiber layer), and the rest is consistent with example 1.
[0130] Comparative Example 4: Pectin polysaccharide nanofiber removed + traditional Chinese medicine extract (fiber + traditional Chinese medicine), the rest is consistent with Example 1.
[0131] Comparative Example 5: Pectin polysaccharide nanofiber removed + Mg-Zn composite nanosystem (fiber + metal composite), the rest is consistent with Example 1.
[0132] The above-mentioned examples related to performance testing:
[0133] I. Antimicrobial performance test
[0134] The inhibition rate of E. coli and S. aureus was tested by inhibition zone method and plate counting method. The samples of Examples 1-5 and Comparative Example 1 were incubated at 37°C for 24h, and the inhibition rate was determined, as shown in the table below:
[0135] Sample E. coli inhibition rate (%) S. aureus inhibition rate (%) Example 1 96.3 95.1 Example 2 95.8 94.6 Example 3 95.5 94.3 Example 4 94.9 94.0 Example 5 95.7 94.8 Comparative Example 1 72.4 69.8
[0136] The above table shows that the nanofiber film of the present application uniformly embedded with Mg-Zn composite nanosystem shows more than 94% inhibition rate on two kinds of bacteria, which is significantly higher than that without nanosystem.
[0137] II. Moisturizing performance and wound healing rate test
[0138] The moisturizing performance was measured by weighing method under constant temperature and humidity (25°C, 50% RH) conditions, and the water retention rate was recorded within 24h; the wound healing rate was tested in a diabetic rat model, according to the international standardized wound area measurement method, the healing rate was calculated on the 7th day and the 14th day of treatment, respectively, and the results are shown in the table below:
[0139] Sample Moisture retention rate (24h, %) Healing rate (7 days, %) Healing rate (14 days, %) Example 1 82 63 92 Example 2 80 61 91 Example 3 79 60 90 Example 4 78 59 89 Example 5 81 62 91 Comparative Example 2 64 42 68
[0140] The results show that with double crosslinking and reasonable moisturizing agent ratio, the dressing of the present application significantly improves the moisturizing capacity while maintaining good antibacterial property, thereby promoting the rapid healing of diabetic wounds.
[0141] III. Mechanical property test
[0142] The tensile strength and elongation at break were measured by electronic tensile testing machine (tensile speed 10 mm / min), and the results are shown in the table below:
[0143] Sample Tensile strength (MPa) Elongation at break (%) Example 1 5.6 43 Example 2 5.4 45 Example 3 5.3 44 Example 4 5.2 42 Example 5 5.5 43
[0144] The above examples all show excellent mechanical strength, meeting the mechanical stability requirements of the dressing during operation and use.
[0145] To further verify the comprehensive effect of the traditional Chinese medicine polysaccharide dressing in the healing of diabetic wounds in the present application, the following in vitro and in vivo experiments were conducted on the preferred embodiments of Example 1 and Example 3 to test their performance in drug release, cell compatibility, antioxidant capacity, matrix metalloproteinase regulation, and wound healing in animal models.
[0146] IV. In vitro drug release performance
[0147] Method: The release curve of the Cortex Phellodendri extract was detected by the dialysis bag method in PBS (pH 7.4) at 37°C, and the absorbance (λ = 370 nm) was measured at regular intervals to calculate the cumulative release rate.
[0148] Results: Both preferred embodiments showed a pattern of slow release in the early stage and stable release in the later stage, with a cumulative release rate of about 30-35% in the first 12 hours, 85-90% at 72 hours, and close to the platform at 120 hours. Compared with the ungrafted modified comparative example, the release curve was smoother, and the burst effect was significantly reduced.
[0149] Conclusion: Double crosslinking and graft modification can stabilize the distribution of drugs in nanofibers, and combined with gel embedding, long-acting controlled release can be achieved.
[0150] V. Cell compatibility (MTT and Live / Dead)
[0151] Method: Human skin fibroblasts (HSF) were cultured in dressing extract for 24 h, 48 h, and 72 h, and MTT was used to detect cell survival rate, and Calcein-AM / PI double staining was used to observe the ratio of live / dead cells.
[0152] Results: MTT detection showed that the cell survival rate of the preferred embodiments was >95% within 72 h, with no significant difference from the blank control (p > 0.05).
[0153] Live / Dead staining results showed that the proportion of green fluorescence (live cells) was >97%, and there was no large area of red (dead cells) signal.
[0154] Conclusion: Low residual glutaraldehyde treatment and the biocompatibility of material components ensure that the dressing has no significant toxicity to cells.
[0155] VI. Antioxidant capacity (ROS inhibition)
[0156] Method: DCFH-DA fluorescent probe was used to detect the level of peroxide, and fibroblasts were exposed to a high-sugar (25 mM) environment, and each sample extract was added and cultured for 48 h, and the intracellular ROS fluorescence intensity was detected.
[0157] Results: The ROS level of the preferred embodiments was reduced by about 45-55% compared with the comparative example (p < 0.01).
[0158] The presence of the Mg-Zn complex nano-system in the dressing is considered to help scavenge free radicals and reduce oxidative stress damage.
[0159] Conclusion: The dressing has significant antioxidant capacity, which is conducive to improving the chronic inflammatory environment of diabetic wounds.
[0160] Seven, anti-MMP-9 expression (Western Blot / RT-qPCR)
[0161] Method: The wound tissue of the diabetic rat model was taken, and after protein and RNA extraction, Western Blot and RT-qPCR were performed to detect the expression levels of MMP-9 protein and mRNA.
[0162] Results: The MMP-9 protein expression of the preferred embodiment treatment group was reduced by about 50%, and the mRNA expression was reduced by about 48%, which was significantly different from the comparative example (p<0.01);
[0163] The reduction of MMP-9 is related to the reduction of collagen degradation and the acceleration of granulation tissue formation;
[0164] Conclusion: The dressing of the present application can significantly down-regulate MMP-9, promote the stability of extracellular matrix, and improve the tissue repair environment.
[0165] Eight, small animal wound healing experiment (diabetic model)
[0166] Method: Diabetic rats modeled by STZ were used to form a 1.0 cm diameter wound by full-thickness skin excision, and the preferred embodiment dressing, the comparative example dressing and the blank control were applied respectively.
[0167] Results: On the 7th day, the healing rate of the preferred embodiment group was 63-65%, the comparative example was about 42%, and the blank control was about 35%; on the 14th day, the healing rate of the preferred embodiment group was 90-92%, the comparative example was 68%, and the blank control was 55%.
[0168] Histology (HE, Masson staining) showed that the epidermis of the preferred embodiment group was complete, the collagen deposition was dense and arranged in order, and the inflammatory cells were significantly reduced.
[0169] Conclusion: The preferred embodiment can significantly accelerate the closure of diabetic wounds and improve the quality of tissue reconstruction in animal models.
[0170] Nine, verification of the effect of the composite system:
[0171] Method: Four groups of controls were set up:
[0172] ① Pectic polysaccharide nanofiber only (comparative example 3); ② Pectic polysaccharide nanofiber + traditional Chinese medicine extract (comparative example 4); ③ Pectic polysaccharide nanofiber + Mg-Zn composite nanosystem (comparative example 5); ④ Pectic polysaccharide nanofiber + traditional Chinese medicine extract + Mg-Zn composite nanosystem (example 1). The ROS inhibition rate, MMP-9 protein and mRNA expression, and wound healing rate of diabetic rats of each group were detected under the same conditions;
[0173] The results show that the ternary system performs best in various indicators, and its effect exceeds the sum of the effects of single components and double components (Bliss independence calculation), and the system of the application has significant synergistic effect.
[0174] The diabetic wound is in a high oxidative stress and high inflammation state for a long time, and ROS and MMP-9 are key molecular factors causing delayed healing: excessive ROS can damage cell membranes and proteins, induce cell apoptosis, and hinder granulation tissue formation; overexpression of MMP-9 will continuously degrade collagen and matrix, resulting in difficulty in closing the wound.
[0175] In summary, the dressing of the application improves the healing environment synergistically through the following mechanisms:
[0176] ① Double crosslinking + graft modification → stable drug release, maintain sustained therapeutic concentration;
[0177] ② Composite nanosystem → provide antibacterial and antioxidant functions, reduce ROS levels;
[0178] ③ Traditional Chinese medicine extract (corkwood and the like) → anti-inflammatory, inhibit MMP-9 expression;
[0179] ④ Optimize the combination of moisturizers → maintain a moist healing environment, promote cell migration and ECM reconstruction.
[0180] The above description of disclosed examples enables those skilled in the art to carry out or use the present application. Various modifications to these examples will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other examples without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these examples shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A traditional Chinese medicine polysaccharide dressing for healing diabetic wounds, characterized in that, The dressing is composed of pectin polysaccharide nanofibers, a composite gel matrix, and additives; The composite gel matrix is a porous network gel structure that embeds traditional Chinese medicine extracts. The pectin polysaccharide nanofibers are formed by electrospinning pectin polysaccharide and polymers under the action of crosslinking agents and surfactants. The pectin polysaccharide is selected from dragon fruit peel pectin, orange peel pectin, and apple peel pectin. The additive is one of the following: adhesive, humectant, compatibilizer, or surface modifier; The herbal extracts include one or more of the following: Phellodendron bark extract, Gardenia fruit extract, and naringin extract; The herbal polysaccharide dressing is in the form of a film or patch, with a thickness of 0.3-1.2 mm.
2. The traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 1, characterized in that, The polymer is one of polyvinyl alcohol (PVA), polyethylene oxide (PEO), chitosan, chitin, or gelatin.
3. The traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 1, characterized in that, The crosslinking agent includes one of calcium ions, glutaraldehyde, or adipate dihydrazide; the surfactant is Triton X-100.
4. A traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 1, characterized in that, The adhesive is low molecular weight polyvinyl alcohol or hydroxypropyl methylcellulose; the humectant is glycerin or sodium hyaluronate; the compatibilizer is polyethylene oxide or polyethylene glycol; and the surface modifier includes one or more of low-temperature plasma, acrylic acid, and glycidyl acrylate.
5. A method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing as described in any one of claims 1-4, characterized in that, Includes the following steps: S1: Extract dragon fruit pectin polysaccharide, concentrate the pectin solution, precipitate with alcohol, dry and pulverize it into pectin polysaccharide dry powder for later use; S2: The pectin polysaccharide dry powder, at least one polymer, and at least one crosslinking agent are added to a solvent, wherein the solvent is water or a water / alcohol mixture, and DMSO, a co-solvent, is added. The mixture is stirred and heated until it is uniformly dissolved or dispersed to obtain a solution. S3: Electrospin the solution to obtain polysaccharide nanofibers; S4: Surface modification treatment is performed on the polysaccharide nanofibers to introduce active functional groups; S5: The modified polysaccharide nanofibers were chemically grafted, and Mg-Zn composite nanosystems were embedded in the grafting process to make them uniformly distributed in the nanofiber layer. S6: Prepare a composite gel matrix by embedding the Chinese herbal extract in a gel matrix using an ultrasonic-assisted swelling method or a freeze-drying method. Add the adhesive, moisturizer and compatibilizer to the composite gel matrix in sequence, stir evenly, and then combine it with the nanofiber layer obtained in step S5 by coating, impregnation or lamination. Finally, freeze-dry or gently dry to form a dressing.
6. The method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 5, characterized in that, The nanofibers described in S5 are chemically grafted with acrylic acid or glycidyl acrylate, with the grafted monomer accounting for 1-10 mol of the available functional groups on the surface.
7. The method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 5, characterized in that, In step S2, the concentration of the pectin solution is 6-10 wt%.
8. The method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 5, characterized in that, In step S6, the amount of compatibilizer added is 1-10 wt% of the total mass of the dressing; the amount of moisturizer added is 0.1-15 wt% of the total mass of the dressing; and the amount of adhesive added is 2-8 wt% of the total mass of the dressing.
9. A method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 5, characterized in that, In step S3, the electrospinning voltage is 15-25kV, the collection distance is 10-20cm, the flow rate is 0.2-1.0mL / h, the ambient temperature is 20-40℃, the relative humidity is 30-70%, and the spinning time is 1-3h / layer; the receiving speed is 80-120r / min, the translation speed is 280-320mm / min, the crosslinking temperature is 25-50℃, and the crosslinking time is 10min-24h.
10. A method for preparing a traditional Chinese medicine polysaccharide dressing for diabetic wound healing according to claim 5, characterized in that, In step S2, the mass ratio of polysaccharide to polymer is 1:(1-4), and the average diameter of the obtained nanofibers is 100-500 nm; the concentration of the traditional Chinese medicine extract is 1-5 wt% of the dry weight of the gel matrix.